The features and factors influencing the effectiveness of advertising activities and TV companies of Sughd region of the Republic of Tajikistan - A. A. Urunov; M. X. Kosimova (Управление)
The essence of television advertising has been considered and the main factors, that can affect the efficiency of advertising activities of companies, have been identified. During the study, the rating of TV companies operating in the Sughd region of the Republic of Tajikistan has been determined, indices of conformity of these channels to the target audience by sex and age categories have been found. Also, by the analysis of viewing time in the context of age and gender of TV viewers, the time of the best out of advertising on the air has been set, that is, the time interval when the maximum number of viewers gathers at their TV sets. For the study region, prime time is in the morning from 6:00 to 8:00, in the evening-from 18:00 to 22:30.It has been established that the performance of TV advertising is influenced by the cost of one spot of advertising. Therefore, it has been evaluated and the rating of state and independent television channels by audience has been determined, and the technology for calculating advertising costs, which determine the effectiveness of advertising activities of companies, has been proposed.Peculiarities of organization of effective advertising activity of companies of Sughd region of the Republic of Tajikistan on oligopolistic market of body and radio services have been revealed. A methodology for calculating indicators characterizing the main factors affecting the efficiency of advertising activities of companies in the Sughd region of the Republic of Tajikistan has been developed.The results of the study can be used in the processes of planning and developing the broadcasting network of TV channels, as well as with success can be applied by players in the market to obtain the best effect of advertising on their products. In addition, the results of the study can be used for the purpose of state regulation of the oligopolistic market of TV and radio services in the Republic of Tajikistan.